Modern Trends in Occupational Safety - Shodmonov Golib Dustmurodovich (Lembaga Yasin AlSys, 2026)
Ensuring workplace safety, reducing occupational diseases, and preventing emergencies in industrial processes are increasingly urgent challenges in modern production environments. This article aims to analyze contemporary trends in occupational safety, with particular attention to the practical application of new technologies, digital transformation, automated monitoring systems, and modern occupational safety standards grounded in international and national experience. Using a scientific analysis of current developments and practices in the field, the study examines how digital tools, real-time monitoring, and updated regulatory frameworks can be integrated to strengthen occupational safety systems. The analysis highlights that the strategic implementation of automated monitoring and technology-enabled safety engineering supports more proactive identification and control of industrial hazards, thereby improving the efficiency of occupational safety management, protecting workers’ health, and ensuring safer production processes. The study concludes that aligning organizational practices with modern technological solutions and contemporary safety standards is essential for advancing occupational safety performance. The findings contribute to the ongoing discourse on occupational safety by synthesizing emerging technological and regulatory trends and providing practical recommendations for organizations to enhance risk management, reinforce safety culture, and systematically safeguard worker health.